The Role of Customer Engagement in Enhancing Passenger Loyalty in IndonesianAirline Industry: Relationship Marketing Approach - Hapsari, Raditha; Clemes, Michael D; Dean, David (Department of Management, Faculty of Economics and Business, Brawijaya University, 2015)
Scholars and practitioners agree that organisations cannot rely on transactional marketing since customers demand more personalized goods and services. Consequently, organisations need to build a relationships based on a mutual exchange with their customers to satisfy their needs and wants and customer relationship emerged to enhance long-term customer profitability. Customer perceived value have been widely accepted as important antecedents improving customer loyalty. However, only a few published studies have the integrated customer engagement construct with the other important marketing constructs to examine the interrelationship among them. This research aims to examine the interrelationships among perceived value, customer engagement and customer loyalty. Focus group discussions, and a survey of 250 Indonesian airline passengers in East Java Province, Indonesia, were conducted to satisfy the research objectives. In order to carry out a comprehensive investigation of the relationship between variables, a quantitative approach is used in this study. The methods used to analyse the data are Confirmatory Factor Analysis (CFA) to test the model fit and Structural Equation Modelling (SEM) to test the hypothesis. Sobel’s test is also used to test the mediating role of customer engagement. The findings of this study indicate while customer perceived value consistently influences loyalty, customer engagement is also proven to be an antecedent of loyalty. Furthermore, customer engagement is also proven to play a mediating role which strengthens the relationship between perceived value and loyalty. The results of the empirical analysis is supported by previous studies that suggest customer engagement is a new construct that has an important role to play in enhancing passenger loyalty.